Consistent mutational paths predict eukaryotic thermostability - Noort, Vera van; Bradatsch, Bettina; Arumugam, Manimozhiyan; Amlacher, Stefan; Bange, Gert; Creevey, Chris; Falk, Sebastian; Mende, Daniel Richard; Sinning, Irmgard; Hurt, Ed; Bork, Peer (BMC evolutionary biology, 2013)
Proteomes of thermophilic prokaryotes have been instrumental in structural biology and successfully exploited in biotechnology, however many proteins required for eukaryotic cell function are absent from bacteria or archaea. With Chaetomium thermophilum, Thielavia terrestris and Thielavia heterothallica three genome sequences of thermophilic eukaryotes have been published.
Gesehen am 21.02.2022